Value Challenge: A Bottoms-Up Approach to Minimizing Cost and Waste in Orthopaedic Surgery. Issue 2 (12th April 2023) - Chen, Kallie J.; Rascoe, Alexander; Su, Charles A.; Benedick, Alex; Furdock, Ryan J.; Sinkler, Margaret A.; Vallier, Heather A.
Abstract : Background: Astronomical increases in medical expenses and waste produce widespread financial and environmental impacts. Minor changes to minimize costs within orthopaedics, the most used surgical subspecialty, could result in substantial savings. However, few orthopaedic surgeons are educated or experienced to implement cost containment strategies. This study aims to investigate cost containment opportunities and provide a framework for educating and incorporating residents into cost-saving initiatives. Methods: Orthopaedic surgical residents from an academic program with a Level I trauma center were queried during 2019 to 2022 regarding suggestions for cost containment opportunities. Based on feasibility and the estimated impact, 7 responses were selected to undergo cost-saving analyses. Results: The proposed initiatives fell into 2 categories: minimizing waste and optimizing patient care. Eliminating nonessential physical therapy/occupational therapy consults led to the greatest estimated savings (8.6M charges/year), followed by conserving reusable drill bits (2.2M/year) and reducing computed tomography scans on lower extremity injuries (446K/year). Conclusion: Current medical training provides limited formal education on cost-effective care. Efforts to mitigate the growing financial and environmental costs of health care should include encouraging and incorporating resident feedback into cost reduction strategies. This tactic will likely have a positive impact on the behavior of such resident surgeons as they enter practice and have more awareness of costs and value. Level of Evidence: V (cost-minimization study)